Inverted bone block for a mandibular lateral ridge augmentation: a case report - AlRowis, Raed; Said, Sherif; Alaqeely, Razan; Albeshri, Sultan; Greenstein, Gary (Journal of the Pakistan Medical Association, 2024)
The purpose of this report is to describe an original technique for bone grafting using an inverted autogenous bone block taken from the same edentulous site that was to be implanted. A 54-year-old female presented for replacement of a missing lower premolar. Clinical and radiographical assessments revealed a deficiency in the width of the alveolar ridge. It was decided to expand the edentate area using an inverted bone block. The graft was harvested from the same edentate site that was to be implanted. The crestal bone width after nine months of healing was increased, and an implant was placed. An autogenous inverted bone block can be used as a bone grafting procedure to augment some bone-deficient sites prior to dental implantations. ---Continue